On the synergy of urban plan - Zuziak, Zbigniew (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
In this paper the interpretation of synergic effects of planning decisions is discussed in the context of urban development strategies and respective attributes of urban plan. The author presents the concept of urban planning formula according to the model named as SAS (acronym from: strategies, actors, structures). This concept refers to urban strategies requiring new urban policy tools and even the reform of existing land use controls system. These changes should allow for better logical connections between spatial planning, strategic planning and urban design. Regarding potentials for inducing synergic effect of urban development as the assessment criterion of the plan, the author discusses the attributes of this plan which are appropriate to stimulate synergic functional links between the elements of land use arrangement, designed in a given planning document, and respective changes in socio-economic and cultural space. Two situations were identified as circumstances generating such effects. First type of such preconditions is described as the postulate to provide clear structural relations between strategic projects and “urbanistic construction” defined as the layout of main physical elements crystalizing spatial structure of the territory covered by the plan. Second significant type of preconditions for achieving synergic effects of the plan depends on the type of urban development strategies including the implementation strategy of key projects. Lessons learned from the cases of good practice in the area of operational urbanism indicate that mutually beneficial effects of interactions between key urban projects can be observed in case of implementation strategies where the respective rules of implementation are clearly defined with regard to urban construction of the planned land use layout. Significant role is also played here by the consistent implementation of the model defined in the long term vision for city development. Such a situation can be exemplified by the principles of urban development strategy defined for metropolitan Copenhagen in the concept known as the “Finger Plan”.